1996
DOI: 10.1029/96gl02450
|View full text |Cite
|
Sign up to set email alerts
|

A new model for the emplacement of Columbia River basalts as large, inflated Pahoehoe Lava Flow Fields

Abstract: Extensive flows of the Columbia River Basalt (CRB) Group in Washington, Oregon, and Idaho are dominantly inflated compound pahoehoe sheet lavas. Early studies recognized that CRB lavas are compound pahoehoe flows, with textures suggesting low flow velocities, but it was thought that the great thickness and extent of the major flows required very rapid emplacement as turbulent floods of lava over a period of days or weeks. However, small volume (< 1 km³) compound pahoehoe flows on Kilauea, Hawai'i, demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
148
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(158 citation statements)
references
References 21 publications
7
148
0
3
Order By: Relevance
“…Although the vent sources for these lavas have yet to be identified. By other terranes, Allen and McPhie (2002) suggested that widespread outf low would be promoted by eruption from several vents along a fissure rather than from point-source vents, a relationship that is well demonstrated in flood basalt provinces (e.g., Self et al, 1996). From a chemical point of view, the Las Lozas rocks plot in diagrams in the subalkaline/tholeiitic (rhyolites), alkaline basalts (basalts) and alkaline (trachytes) fields.…”
Section: Disscusionmentioning
confidence: 99%
“…Although the vent sources for these lavas have yet to be identified. By other terranes, Allen and McPhie (2002) suggested that widespread outf low would be promoted by eruption from several vents along a fissure rather than from point-source vents, a relationship that is well demonstrated in flood basalt provinces (e.g., Self et al, 1996). From a chemical point of view, the Las Lozas rocks plot in diagrams in the subalkaline/tholeiitic (rhyolites), alkaline basalts (basalts) and alkaline (trachytes) fields.…”
Section: Disscusionmentioning
confidence: 99%
“…mechanism of these eruptions, which in turn has enhanced our understanding of larger-scale flood basalt eruptions on Earth and Mars (e.g. Larsen, 1979Larsen, , 2000Thordarson and Self, 1993, 1998Self et al, 1996Self et al, , 1997Thordarson et al, , 2003aKeszthelyi et al, 2000Keszthelyi et al, , 2004Guilbaud et al, 2005). It has also demonstrated that over the last 1130 years, these events are the most significant of Icelandic eruptions in terms of environmental and climatic effects because of the huge amount of sulphur (100-250 Mt of SO 2 ) they release into the atmosphere (Thorarinsson, 1979;Metrich et al, 1991;Stothers, 1996Stothers, , 1998Thordarson et al, , 2001Thordarson et al, , 2003bOman et al, 2006) The high-discharge flood lava events are prolonged fissure eruptions that last for months to years and feature numerous eruption episodes (Fig.…”
Section: Effusive Eruptionsmentioning
confidence: 99%
“…We assume that a surface crust forms quickly and the flow is completely covered. We assume eruption at a depth of-1 km below sea level and flow over a seafloor with a slope of 1 in 1000 (similar to that assumed for eraplacement of the Columbia River Basalt [Self et al, 1996; 1997]). For runs over massive substrates (e.g., basalt), it is assumed there was no intergranular water in the substrate (fw = 0).…”
Section: Assumptionsmentioning
confidence: 99%